2023
DOI: 10.3389/fsurg.2022.1004642
|View full text |Cite
|
Sign up to set email alerts
|

Will the adjustment of insertional pedicle screw positions affect the risk of adjacent segment diseases biomechanically? An in-silico study

Abstract: BackgroundThe fixation-induced biomechanical deterioration will increase the risk of adjacent segment diseases (ASD) after lumbar interbody fusion with Bilateral pedicle screw (BPS) fixation. The accurate adjustment of insertional pedicle screw positions is possible, and published studies have reported its mechanical effects. However, no studies clarified that adjusting insertional screw positions would affect the postoperative biomechanical environment and the risk of ASD. The objective of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…To date, most studies have found that insertional screw positions affect surgical segment stiffness and local stress distribution, which are closely associated with the incidence of CS. 16 Newcomb et al suggested that angulations in both the sagittal and axial planes affected fixation strength during posterior spine fixation. 17 For OLIF‐AF, screw placement is not restricted by the pedicle; thus, theoretically, anterolateral screws can be placed in different trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies have found that insertional screw positions affect surgical segment stiffness and local stress distribution, which are closely associated with the incidence of CS. 16 Newcomb et al suggested that angulations in both the sagittal and axial planes affected fixation strength during posterior spine fixation. 17 For OLIF‐AF, screw placement is not restricted by the pedicle; thus, theoretically, anterolateral screws can be placed in different trajectories.…”
Section: Introductionmentioning
confidence: 99%